Sámi Shamanism, Cosmology and Art as Systems of Embedded Knowledge - Joy, Francis (fi=Lapin yliopisto|en=University of Lapland|, 2018)
Scientific research into Sámi shamanism and cosmology over the past several decades has brought forth an intricate body of knowledge, insights and understanding concerning the religious and cultural practice of Europe’s indigenous people from Sápmi, which is rooted in a sacrificial tradition that transverses back into prehistory. The remnants of this tradition are evident through various art forms, depicted as systems of embedded traditional knowledge by the Sámi noaidi or shaman, who is known as a tradition bearer. The noaidi’s art, which is best known from the divination drums of the seventeenth and eighteenth centuries, collected during the midst of colonialism, has prompted a much broader investigation of both Sámi history, religion and religious practices for the following reasons. More recently, tangible evidence has emerged in historical studies, prompting further research concerning a series of parallels between noaidi art and prehistoric rock art; especially rock paintings in Finland and at the extensive Alta rock art site in Finnmark, northern Norway. Because of the temporal distance between the two sources of art, the subject matter remains ambiguous on account of the historical gaps between the materials. Despite these disputes, questions have come to light as to whether or not the rock art as a knowledge system, has influenced the ways the symbolism and figures have been drawn on the noaidi drums heads, thereby indicating the transmission or oral tradition and culture and thus, outlining a possible survival of an ancient religion and cosmology? Henceforth, prompting a series of questions in relation to the cultural heritage of rock art against the present cultural contexts, which suggests ownership by the nation states of Finland, Sweden and Norway. With regard to the study of noaidi drums, their artistic content and the transmission of traditional knowledge and culture, new forms of drums are emerging throughout northern Finland, Sweden, Norway and the Kola Peninsula in south-west Russia. Some of ...